Aging and social security system in Pakistan: policy challenges, opportunities, and role of China–Pakistan Economic Corridor (CPEC). Issue 9 (2nd September 2018) - Ahmad, Riaz; Mi, Hong; Keyao, Ren; Khan, Khalid; Navid, Khan
ABSTRACT: The purpose of this research is to highlight the aging and elderly care in Pakistan, a country considered the seventh most populous country in the world with an estimated population of 220 million people (citation, 2017). In 2013, Pakistan signed a MoU with China for 56 billion in US$ to create opportunities for the youngsters, but there was no story of opportunity included for the senior citizens. An attempt has been made to raise awareness of the plight of seniors to the Pakistan Government's attention; however since there is no formal policy dedicated to elders from the Chinese mega MoU and political instability, only little has been accomplished to better the lives of older adults. Modernization has had a major impact on the life of older Pakistani, and not always a positive effect. This research focuses on the important issues that are making the lives of senior citizens more difficult. The issues include psychological factors, anxiety, physical issues, and environmental issues. The research concludes while many factors are making the lives of senior citizens problematic, seniors are still living a satisfied life because they are not depending on their children or others. Senior citizens demand and desire time with their children and grandchildren. Increases found in elders' psychological problems are likely correlated with modernization. Unfortunately, the China–Pakistan Economic Corridor (CPEC) and the mega project remain totally for the younger population with no economic prospects for elders to directly benefit. Thus, the question remains what will be the outcome for Pakistani seniors?